Supporting a statewide policy consideration: Virtual advancing educational leadership training during COVID-19 - Elfarargy, Hamada; Irby, Beverly J.; Abdelrahman, Nahed; Carol Webb, Gwendolyn; Abney, Angela; Holley, Susan; Villarreal, Elsa; Fahrenwald, Carl (Frontiers in Education, 2022)
COVID-19 pandemic was and continues to be a shock and a challenge to the entire world. This health and safety challenge found its way into the world of higher education, even in programs that were already delivered in online environments. In this study, we examined the perceptions of 79 developing principals enrolled in a Master of Education Degree program in Educational Administration at XX University in the United States as they processed the efficacy of a virtual professional development (VPD) leadership for a state certificate in Advancing Educational Leadership (AEL). The state agency has required AEL as a three-day state-mandated face-to-face training which is a basic requirement for school leaders who evaluate teachers. In fact, per state policy, AEL was delivered in a face-to-face format since it began in 2015, but was transformed to a VPD format in 2020, for the first time, as a response to safety concerns resulting from the COVID-19 pandemic. The Texas Education Agency indicated that the training would go back to a face-to-face format after Fall, 2021; however, recently the Agency determined that virtual training could continue, along with face-to-face. Initially, this study was conducted to add information to the policy consideration as to whether to leave the option open for university principal preparation programs to offer the AEL virtually or face-to-face; however, with the alteration of the policy and with the findings of the study, we now provide empirical support, based on a a concurrent triangulation mixed methods design, for the Agency’s policy action. This study might be the first published in support of this AEL training policy.